Inseparability Of Compound Words - KarimovaUmida; Poyonova Sadoqat; Ohunjonova Ominaxon; Saxaddinova Nilufar (Genius Journals, 2023)
This article is depending on difference between words and stems even when they coincide morphemically is especially evident in compound adjectives proper.
Keywords: grammatical; polysyllabic; solidly